The Effect of Guided Inquiry Learning Method on Science Learning Outcomes in Grade V Students of SD Negeri 1 Amparita - Asman L; Ni Wayan Sariani Binawati (Jayapangus Press, 2023)
Learning is still centered on the teacher so that students are still passive. Lack of teacher attention to the potential of students in terms of group cooperation, building their own knowledge by collecting data or hypothesizing and less involved in activities that are fun and move children's motoric. This is because the teacher has not used innovative learning methods so that it causes low student learning outcomes, so research is needed to test this. The purpose of this study was to determine the effect of guided inquiry learning method on science learning outcomes of grade V students of UPT SD Negeri 1 Amparita, Sidrap Regency. This research approach is quantitative with experimental type. This study consists of two variables, namely the guided inquiry learning method as the independent variable and science learning outcomes as the dependent variable, with a research design of Nonequivalent Control Group Design. The population used was all grade V students, namely class Va as an experimental class with 27 students and class Vb as a control class with 26 students without being randomized. The data obtained were analyzed with descriptive statistics and inferential statistics. The results of descriptive analysis showed that the increase in the average value of science learning outcomes of the experimental class was higher than the average science learning outcomes of the control class. The t-test analysis using the Paired Samples T-Test test shows that the significance value of 0.000 is smaller than α = 0.05 and the t-count is greater than the t-table, thus H0 is rejected and H1 is accepted. It can be concluded that the guided inquiry learning method has an effect on science learning outcomes about the human respiratory system in class V UPT SD Negeri 1 Amparita Sidrap Regency.